Діагноз доби: психічна хвороба в драматургії Володимира Винниченка як метафора буття в епоху модерну - Ганошенко, Юрій Анатолійович (Запорізький державний медичний університет, 2020)
У статті розглядається проблема медикалізації драматичного метатексту драм Володимира Винниченка3 та функціонування у його текстах психічного захворювання як певного конструенту поетики і метафори буття розщепленої людини епохи Модерну. Volodymyr Vynnychenko is one of the most prominent Ukrainian artists and thinkers of the early twentieth century. His works reflect the most significant problems in the development of the Ukrainian culture of the Age of Modern. In the center of his dramatic works, there is a problem of a new personality with a demolished behavioral and ideological traditional canon. Global cultural changes destroy ethical and psychological constants of the human individuality. The biographical in the writer's texts is closely intertwined with the common cultural pathogenic phenomena and the search for new forms of expression in the artistic discourse of the era. The article deals with the problem of the medicalization of the dramatic metatext of Volodymyr Vynnychenko's plays and the functioning of a mental illness in his texts as a certain poetic construct, an important factor in the development of author's meanings, and a significantly important component of the author's artistic code. The Mental illness becomes a permanent component of Volodymyr Vynnychenko's dramaturgy and a common characteristic of the majority of dramatis personae and becomes a universal metaphor for the being of a split man in the Age of Modern.
Keywords: Винниченко; модернізм; психічна хвороба; драматургія; психосфера; Vynnychenko; modernism; mental illness; dramaturgy; psychosphere